Geothermal Energy Utilization in the Kamojang Nature Reserve, West Java, Indonesia - Dahlan, Endes N; Putiksari, Vella; Prasetyo, Lilik Budi (Forum Geografi, 2015)
Geothermal energy activities are allegedly disturbing Kamojang Nature Reserve by clearing the forest. Actually, the national park according to the Law No. 41 of 1999, must not jeopardize the preservation of germplasm in it. Meanwhile, the utilization of geothermal power plant in the area is also required to meet the electricity demand in Indonesia. Land clearing as one of the activity of exploration and exploitation of geothermal coupled with the increasing of humanâs activity inside the forest caused widespread deforestation. Since there is a geothermal energy project inside the Kamojang Nature Reserve, then the aim of this study is to analysis the land cover change at Kamojang Nature Reserve from year 2000 until 2011. The research showed that the type of land cover was dominated by forest for about 4231.3 ha with forest cover percentage around 51.17%. Aside of that, the land cover change caused by exploration and exploitation of Pertamina Geothermal Energy was 60.2 ha (8.90 %), while the changes caused by human activities was 614.46 ha (91.10 %). Based on these results, replanting had been done to overcome the worse effect from each activities. The extent of reforestation and enrichment conducted by PGE was 680.58 ha by involving the society who live in surrounding area.